2021
DOI: 10.1162/nol_a_00044
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism: A Neurocognitive Exercise in Managing Uncertainty

Abstract: Bilinguals have distinct linguistic experiences relative to monolinguals, stemming from interactions with the environment and individuals therein. Theories of language control hypothesize that these experiences play a role in adapting the neurocognitive systems responsible for control. Here we posit a potential mechanism for these adaptations, namely that bilinguals face additional language-related uncertainties on top of other ambiguities that regularly occur in language, such as lexical and syntactic competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 119 publications
0
20
0
Order By: Relevance
“…That is, when all available languages are used in a fully integrated manner, the unpredictability of which language to use increases as the number of available languages increases. The extent to which the management of this unpredictability is needed is argued to drive neurocognitive adaptations, which consequently increase behavioral efficiency and optimize decision making ( Gullifer and Titone, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…That is, when all available languages are used in a fully integrated manner, the unpredictability of which language to use increases as the number of available languages increases. The extent to which the management of this unpredictability is needed is argued to drive neurocognitive adaptations, which consequently increase behavioral efficiency and optimize decision making ( Gullifer and Titone, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, while we primarily focused on how multilinguals comprehend written materials, it is important to recall an important component of most health literacy frameworks corresponds to the oral communicative skills of people. These emotionality effects may also translate to interpreter-mediated medical interactions (e.g., Hordyk et al, 2017;López, 2020;Zhao et al, 2021) by inhibiting the production and comprehension processes of interpreters under stressful, incongruent, or emotionally ambivalent situations (see link between Panels A and Language barriers Panel in online supplemental materials Figure S1; also see Baquiran & Nicoladis, 2020;Gullifer & Titone, 2021;Itzhak et al, 2017).…”
Section: Moving Forwardmentioning
confidence: 99%
“…have argued that language entropy is ideal for synthesizing theoretically relevant variables on a continuum while accounting for the social diversity and interactional context of language usage. More recently, studies using language entropy variables have shown the impact of bilingualism on cognitive and neural processes Sulpizio et al, 2020;Li et al, 2020;Gullifer and Titone, 2021).…”
Section: Mathematical and Statistical Ways To Combine Bilingual Varia...mentioning
confidence: 99%